Subtract 6t from each side of the equation. Subtraction Property of Equality

\(8t+5-6t=6t+1-6t\)

Simplify

\(2t+5=1\)

Subtract 5 from each side of the equation. Subtraction Property of Equality

\(2t+5-5=1-5\)

Simplify

\(2t=-4\)

Divide each side of the equation by 2. Division Property of Equality

\(\frac{2}{2}*t=\frac{-4}{2}\)

Simplify

\(t=-2\)

Check solution

\(8(-2)+5=6(-2)+1\)

\(-16+5=-12+1\)

\(-11=-11\)

\(8t+5-6t=6t+1-6t\)

Simplify

\(2t+5=1\)

Subtract 5 from each side of the equation. Subtraction Property of Equality

\(2t+5-5=1-5\)

Simplify

\(2t=-4\)

Divide each side of the equation by 2. Division Property of Equality

\(\frac{2}{2}*t=\frac{-4}{2}\)

Simplify

\(t=-2\)

Check solution

\(8(-2)+5=6(-2)+1\)

\(-16+5=-12+1\)

\(-11=-11\)